PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SQUARE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 11 PADANG - Alatas, Mukti Ali; Rismen, Sefna; Pratiwi, Merina (Pendidikan Matematika, 2013)
The research is based on by less unusually students discuss and construct knowledge received during the learning process, and students low of comprehension of mathematical concept. The research aims to determine students comprehension of mathematical concept by applying cooperative learning Think-Pair-Square better than the students comprehension of mathematical concepts with conventional teaching 8th grade students of State Junior High School 11 Padang. This type of research is experimental research on the subject with a random design. The population is 8th grade students of State Junior High School 11 Padang academic year 2012/2013. Class selected sample is VIII.G class as the experimental class and the control class VIII.B class. The research instrument was the final test in the form of essay test reliability is 0.79084. Hypothesis testing using one side of t-test. Based on the analysis of data obtained thitung=2,83 is less than ttable=1,64, so it can be concluded that the students comprehension of mathematical concept that apply cooperative learning model Think-Pair-Square is better than students comprehension of mathematical concept that apply conventional learning model in class VIII SMP 11 Padang.